Dynamics of associative polymers. Issue 16 (14th March 2018) - Zhang, Zhijie; Chen, Quan; Colby, Ralph H.
Abstract : Current progress in understanding the dynamics of associating polymers is reviewed, with examples including both ionic and hydrogen bonding associations. Abstract : Current progress in understanding the dynamics of associating polymers is reviewed, with examples including both ionic and hydrogen bonding associations. A particular emphasis is placed on quantification of the strength of the interaction that sets the association lifetime. Knowledge of the interaction energy and the number density of associating groups allows a rational understanding of the linear viscoelastic response of many associating polymers.